Arterial stiffness is associated with visceral fat mass in kidney transplanted patients—A nationwide cohort study. Issue 8 (26th August 2018) - von Düring, Marit Elizabeth; Jenssen, Trond; Bollerslev, Jens; Godang, Kristin; Hartmann, Anders; Åsberg, Anders
Abstract: Arterial stiffness, visceral fat, and hyperglycemia are acknowledged risk factors for adverse outcomes after transplantation, but whether arterial stiffness is associated with visceral adipose tissue and hyperglycemia is unknown. We studied 162 non‐diabetic kidney transplant recipients 8‐10 weeks after transplantation. Arterial stiffness was measured as pulse wave velocity (PWV) by SphygmoCor and visceral fat using a validated software applied on DXA scans. Also a standard oral glucose tolerance test was performed. Median PWV was 8.6 m/s (IQR 7.3‐10.4 m/s). Patients in the upper quartile of PWV had 31%‐106% higher visceral fat percentage ( P < 0.001), they were older ( P < 0.001) and had a fasting plasma glucose of 5.8 mmol/L that was higher than in the other quartiles ( P = 0.006). In univariate analysis, visceral fat percentage and age were the parameters strongest associated with PWV ( P < 0.001), but cholesterol and glucose were also significant ( P < 0.05). In multivariate analysis, visceral fat was the only significant predictor of PWV along with age ( P < 0.001). In conclusion, arterial stiffness is significantly associated with visceral fat but not hyperglycemia in non‐diabetic kidney transplant patients. We identified age and VAT as risk variables for arterial stiffness. A potential reversibility of arterial wall stiffness with reduction in VAT needs further study.